(untitled) (Jurnal Simki Economic, 2024)
Jims Honey products are known as an exclusive fashion brand, but when compared to other brands, Jims Honey products have a more affordable price range and are more popular. In the Special Region of Yogyakarta, this study intends to examine how factors including pricing, brand image, lifestyle, and co-branding impact Jims Honey product purchases. The major source of data for this descriptive study is a survey of research participants. Quantitative methods are also employed. One hundred people from the Special Region of Yogyakarta, Indonesia, who were between the ages of 17 and 26 made up the study’s population. Jims Honey product purchases are positively and significantly impacted by pricing and brand perception, according to the study’s findings.